Improving pedestrian safety via the optimization of composite hood structures for automobiles based on the equivalent static load method. (15th September 2017) - Kim, Dong-Hyun; Jung, Ku-Hyun; Kim, Dug-Joong; Park, Sung-Hyeon; Kim, Do-Hyoung; Lim, Jaeyoung; Nam, Byeung-Gun; Kim, Hak-Sung
Abstract: In this study, design optimization of a composite hood for automobiles was carried out to mitigate the impact of pedestrian head injuries based on finite element analysis. Reduced vehicle, headform impactor and single hood models were established to obtain optimal composite hood designs. The carbon fiber reinforced composite (CFRP) and the hybrid Glass fiber reinforced composite (CFRP/GFRP) laminates were selected as composite material candidates. Both stacking angle sequence and topometry of the composite hood were optimized based on the equivalent static load method. After the optimization, the head injury criterion (HIC), deflection and weight were measured to evaluate the performance of the composite hood. The developed CFRP and hybrid CFRP/GFRP type hoods with optimized final design exhibited the improved impact performance and significant weight reduction while satisfying bending and torsion deflection requirements compared to those of conventional steel and aluminum hoods.